2020
DOI: 10.1016/j.psj.2020.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Serological investigation of Ornithobacterium rhinotracheale infection in China

Abstract: Ornithobacterium rhinotracheale ( ORT ) has been associated with avian respiratory disease. On coinfection with other pathogens, ORT can cause serious health problems in avian species, leading to financial losses. To monitor the serologic prevalence of ORT in chicken flocks in China, 1,280 sera were collected to determine ORT antibodies among 64 flocks from 15 provinces of China using a commercial ELISA kit. The overall seroprevalence of ORT among the birds tested was 44.06%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Associations with age of birds, Our results relating to the incidence of QRT infection and age of birds are parallel with those of Xue et al (2020), who found that by increasing the age, the rate of ORT also increased. ORT is a difficult bacterium to be cultured.…”
Section: Discussionsupporting
confidence: 82%
“…Associations with age of birds, Our results relating to the incidence of QRT infection and age of birds are parallel with those of Xue et al (2020), who found that by increasing the age, the rate of ORT also increased. ORT is a difficult bacterium to be cultured.…”
Section: Discussionsupporting
confidence: 82%
“…This observation was confirmed by culturing the suspected colonies on MacConkey's agar medium, which revealed negative results in the presence of ORT [15]. Nevertheless, using the polymerase chain reaction (PCR) diagnostic method has shown to be one of the most important detection methods for ORT due to its proven sensitivity and accuracy compared to traditional isolation methods [12,[15][16][17]. Likewise, for further confirmation of the presence of ORT, 16S rRNA sequencing has been conducted in several studies.…”
Section: Introductionmentioning
confidence: 94%
“…However, these manifestations depended on many factors, such as live viral infection burdens or other bacterial synergism occurring during the infection process. Furthermore, many important factors, such as stock density, bad management, and environmental conditions accounted for infection rates, as the ORT infection was also reported after stress factors like live vaccination [7,12]. Nevertheless, the main characterized symptom of swollen head syndrome (SHS) was observed to be swelling of the head and facial edema, which resulted from accumulating inflammatory exudates beneath the skin of the head [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ornithobacterium rhinotracheale is a small, gram-negative bacillus with rounded ends, which does not form spores or capsules, is poorly cultured by classical bacteriological methods, and its growth is often suppressed by the accompanying microflora (Hauck & Shivaprasad, 2015). The causative agent of ornithobacteriosis is common in Europe and Asia, and poultry are infected in vertical and horizontal ways (Mayahi et al, 2016;Xue et al, 2020). A large variation in ornithobacterium serotypes, the rapid development of circulating strains' resistance, the complex process of isolating the pathogen and setting up a response to antibiotic sensitivity, contributes to the fact that ornithobacteriosis often remains an "undertreated disease".…”
Section: Introductionmentioning
confidence: 99%